2015
DOI: 10.1111/bjh.13658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe ADAMTS13 deficiency on clinical presentation and outcomes in patients with thrombotic microangiopathies: the experience of the Harvard TMA Research Collaborative

Abstract: SummaryThe Harvard TMA Research Collaborative is a multi-institutional registrybased effort to study thrombotic microangiopathies (TMA). Laboratory and clinical parameters were recorded for 254 cases of suspected autoimmune thrombotic thrombocytopenic purpura (TTP). Patients with severe ADAMTS13 deficiency (activity ≤10%, N = 68) were more likely to be young, female and without a history of cancer treatment or transplantation. While all patients with severe deficiency were diagnosed with autoimmune TTP, those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 22 publications
5
100
0
2
Order By: Relevance
“…These cases of TMA comprise a diverse group of conditions, including drug‐associated TMA, transplant‐associated TMA, disseminated intravascular coagulation (DIC), and metastatic cancer, for which data supporting the use of TPE is poor. Despite evidence‐based guidelines recommending against the routine use of TPE for cases of transplant‐ or cancer‐associated TMA, our findings indicate that approximately 20% to 30% of such patients still receive this therapy . Additionally, some have reported that patients with TMA of unclear etiology but without severe ADAMTS13 deficiency appear to benefit from treatment with TPE, while others have shown that these patients can be safely managed without TPE .…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…These cases of TMA comprise a diverse group of conditions, including drug‐associated TMA, transplant‐associated TMA, disseminated intravascular coagulation (DIC), and metastatic cancer, for which data supporting the use of TPE is poor. Despite evidence‐based guidelines recommending against the routine use of TPE for cases of transplant‐ or cancer‐associated TMA, our findings indicate that approximately 20% to 30% of such patients still receive this therapy . Additionally, some have reported that patients with TMA of unclear etiology but without severe ADAMTS13 deficiency appear to benefit from treatment with TPE, while others have shown that these patients can be safely managed without TPE .…”
mentioning
confidence: 56%
“…Subsequently, a FRETS‐based assay utilizing the VWF73 substrate was used for all assays performed at both laboratories. Severe deficiency in ADAMTS13 was defined as an activity level of not more than 10% based on previous work indicating that this cutoff provides excellent sensitivity and specificity for idiopathic TTP …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disorders include idiopathic TTP (which is confirmed by the finding of completely suppressed ADAMTS-13, is less likely to present with profound renal impairment, 30,31 and is typically more responsive to plasma exchange), STEC-HUS, Drug Induced TMA (which includes cases occurring in the post-transplant setting and often calcineurin-inhibitor related), HIV-related, 32 disseminated intravascular coagulation (which can produce a MAHA pattern but as opposed to classic TMA, also engenders coagulopathy), hypertensive emergencies, malignancy-related TMA, 33,34 cobalamin deficiency, 35-38 pregnancy related conditions such as hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome, and others. 39 …”
Section: Diagnosticsmentioning
confidence: 98%
“…TMA ranges from typical thrombotic thrombocytopenic purpura (TTP) to localized renal TMA (1,2). This disease is associated with a broad range of conditions, including infection, organ transplantation, autoimmune disease and pregnancy (3). TMA is also a well-described complication of both cancer and its treatment (4).…”
mentioning
confidence: 99%